The Causal Impact of the Electoral System on Corruption - Abel François; Nicolas Lagios; Pierre-Guillaume Méon (CESifo GmbH, 2024)
We estimate the causal effect of the electoral system on corruption by leveraging a specificity of the French electoral law where the electoral system for municipal councils depends on municipal population. Specifically, municipalities with fewer than 1,000 inhabitants use an individual majority system, while those above this threshold use a proportional list system. Exploiting that discontinuity in a regression discontinuity design and using survey and actual corruption data, we find that the proportional list system results in higher levels of perceived and actual corruption than the individual majority system.
Keywords: D72; D73; 330; corruption; electoral systems; local government